(untitled) (Archaeologia Adriatica, 2022)
The paper analyzes a belt buckle of composite construction found at the Iron Age site of Prozor near Otočac. In its form and construction, it resembles belt buckles from the area of the Dolenjska Hallstatt group, dated to the period of the 6th and 5th centuries BC. The buckle consists of an embossed bronze sheet riveted on an iron plate. Attention is also paid to the source of inspiration for decorative motifs on the buckle - horse figures that are characterized by certain realistic quality that is not typical of other, mostly stylized horse depictions from the Iapodean region.